2010
DOI: 10.1111/j.1464-410x.2009.08955.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐port, single‐operator‐light endoscopic robot‐assisted laparoscopic urology: pilot study in a pig model

Abstract: pneumoperitoneum obtained. An operative laparoscope was introduced and securely held using a novel low-profile robot under foot and/or voice control. Using articulating instruments, each pig had bilateral reconstructive and extirpative renal surgery. Salient intraoperative and postmortem data were recorded. Results were analysed statistically to determine if outcomes improved with surgeon experience. RESULTSFive male farm pigs underwent bilateral partial nephrectomy and bilateral pyeloplasty before a completio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Our results are consistent with a previous study by Crouzet et al for reconstructive and extirpative urological surgery using the porcine model [5]. The authors concluded that with singleport access, the robotic endoscope allows more room for the surgeon compared to an assistant.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with a previous study by Crouzet et al for reconstructive and extirpative urological surgery using the porcine model [5]. The authors concluded that with singleport access, the robotic endoscope allows more room for the surgeon compared to an assistant.…”
Section: Discussionsupporting
confidence: 93%
“…In an attempt to overcome these limitations, Crouzet et al recently presented their initial translational animal study in which a low-profile robot was used to assist one surgeon to complete LESS reconstructive and extirpative renal procedures. 79 After making a 2-cm umbilical incision, through which a single port was placed and pneumoperitoneum obtained , an operative 5-mm 30°rigid high-definition laparoscope was introduced and securely held using a novel low-profile robot under foot and/or voice control (Light Endoscope Holder Robot, LER, EndoControl, Grenoble, France). Using articulating instruments, each pig had bilateral reconstructive partial nephrectomy and bilateral pyeloplasty before a completion bilateral radical nephrectomy.…”
Section: Robotics: the Missing Link Towards Scarless Urological Surgery?mentioning
confidence: 99%
“…In recent times, two innovative techniques have gained much interest as a step towards even less invasive procedures: natural orifice transluminal endoscopic surgery (NOTES), which involves using a natural orifice of the body to perform a surgical procedure, and single‐incision laparoscopic surgery in which the surgical scar is virtually concealed within the umbilicus. Although some reports suggest a promising future for these techniques, most authors have readily conceded that in their current form they are limited by technical constraints3–7.…”
Section: Introductionmentioning
confidence: 99%